2017
DOI: 10.1002/ajoc.201700532
|View full text |Cite
|
Sign up to set email alerts
|

Elemental‐Sulfur‐Promoted C(sp3)−H Activation of Methyl Heteroarenes Leading to Thioamides

Abstract: An approach to access bioactive thioamides was developed based on elemental-sulfur-promoted C(sp 3 )ÀHa ctivation of methylh eteroarenes.T his transformation could successfully furnish as eries of heterocyclic thioamidesw ith excellent yields and it could be conducted on gram scale with good reaction efficiency.M echanistic studies showedt hat methyl heteroarenes reactedw ith dimethylamine released from DMF to form the desired thioamide through elemental-sulfur-promoted CÀHa ctivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 73 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…Next, the screening of polar aprotic solvents such as EtOAc, THF and 1,4-dioxane revealed that THF solvent was superior than the other two solvents as it gave 68% yield of the product. The use of chlorinated solvents such as DCE and TCE and non-polar solvent such as toluene did not increase the product yield (entries [8][9][10]. When PEG 200 was used as the solvent, it rendered the product in 77% yield (entry 11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, the screening of polar aprotic solvents such as EtOAc, THF and 1,4-dioxane revealed that THF solvent was superior than the other two solvents as it gave 68% yield of the product. The use of chlorinated solvents such as DCE and TCE and non-polar solvent such as toluene did not increase the product yield (entries [8][9][10]. When PEG 200 was used as the solvent, it rendered the product in 77% yield (entry 11).…”
Section: Resultsmentioning
confidence: 99%
“…[3] However, shortcomings, such as the use of pyrophoric base and the need of cryogenic temperature, associated with this approach were first overcome by Huang and co-workers by treating 2-methylazaarenes with N-sulfonyl aldimines using Pd(OAc) 2 /1,10-phen catalyst (Scheme 1b). [4] Afterwards, both Brønsted acid [5] and Lewis acid [6][7] catalyzed transformations, as well as transition metalfree [8] and asymmetric [9] approaches have been reported by varying the electrophiles (Scheme 1c). Although these transformations have many benefits, they require the use of corrosive Brønsted acid and homogeneous Lewis acid catalysts and external ligand, and most of the reports were not focused on the recovery of the catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Intermediate V undergoes dehydration and easily converted to intermediate VI . Meanwhile, elemental sulfur undergoes nucleophilic attack by morpholine, to afford polysulfide IV . Then, intermediate IV reacts with intermediate VI to afford intermediate VII .…”
Section: Resultsmentioning
confidence: 99%
“…Then, intermediate IV reacts with intermediate VI to afford intermediate VII . Owing to the presence of the extra hydrogen on the methylene group of the imine, intermediate VII oxidizes to release the final product 4 A in the presence of an amino sulfur species …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation